2017
DOI: 10.1097/md.0000000000005889
|View full text |Cite
|
Sign up to set email alerts
|

The rare ethambutol-induced optic neuropathy

Abstract: Rationale:Ethambutol-induced optic neuropathy (EON) is a well-known complication that results from the use of ethambutol. The ocular manifestations of EON include painless loss of central vision and cecocentral scotomas in the visual field.Patient concerns:A 75-year-old Chinese Han man suffered from this rare ocular disorder because he took ethambutol for about 8 months.Diagnoses:He was diagnosed as EON based on series of ophthalmic examinations performed.Interventions:Since he has stopped taking this drug for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…EMB-induced optic neuropathy is a well-known complication of EMB administration, the severity of which is dose dependent (16). A systematic review showed that the incidence of all visual impairments and permanent visual impairments associated with EMB treatment was 19.2 and 2.3 persons per 1,000 patients, respectively, when the patients were treated with the standard dose for 2 to 9 months (17).…”
Section: Discussionmentioning
confidence: 99%
“…EMB-induced optic neuropathy is a well-known complication of EMB administration, the severity of which is dose dependent (16). A systematic review showed that the incidence of all visual impairments and permanent visual impairments associated with EMB treatment was 19.2 and 2.3 persons per 1,000 patients, respectively, when the patients were treated with the standard dose for 2 to 9 months (17).…”
Section: Discussionmentioning
confidence: 99%
“…6 The time of onset of ehambutol induced optic neuritis is not predictable, but it usually starts between 4 to 12 months after initiation of therapy, but can also occur as early as within days of therapy. 7,9,10 The other factors which can contribute to this adverse effect are the age of the patient, duration of treatment, the renal status, alcohol and smoking habits of the patient, other concurrent illness like hypertension, and diabetes in the patient. 11 Patients usually present with progressive painless loss of vision, identified initially as blurring of vision during reading suggestive of central field defects.…”
Section: Discussionmentioning
confidence: 99%
“…Further, prolonged usage of ethambutol is also associated with deficiencies in vitamins E and B12, which additionally exacerbate the symptoms of optic neuropathy. Most common symptoms of EON include the painless loss of central vision and the presence of cecocentral scotomas in the field of vision [ 126 ]. The majority of patients present with bilateral, symmetric loss of central visual acuity as well as dyschromatopsia [ 125 ].…”
Section: Optic Neuropathy Induced By Toxic Substancesmentioning
confidence: 99%